Regional Financial Capacity, Capital Expenditure, and Economic Growth: Capital Expenditure as a Mediating Variable - Ariza Eka Novianto; Arung Lamba; Halomoan Hutajulu (Goodwood Publishing, 2026)
Purpose: This study examines the effect of regional financial capacity on capital expenditure and economic growth in Biak Numfor Regency, Indonesia, and tests whether capital expenditure mediates the relationship between regional financial capacity and economic growth. Methodology: The study applies a quantitative approach using secondary time series data for the 2015 to 2024 period obtained from the Central Statistics Agency, the Regional Finance Agency, and related institutions. Regional financial capacity is measured through the regional financial independence ratio, the effectiveness ratio of regional own-source revenue, the efficiency ratio, and the fiscal decentralization degree ratio, capital expenditure is measured through its realized allocation, and economic growth is measured through the annual growth rate of gross regional domestic product at constant prices. Data were analyzed using descriptive statistics, path analysis, and the Sobel test. Results: Regional financial capacity in Biak Numfor Regency tends to be low and fluctuating. Regional financial capacity has a positive and significant effect on capital expenditure and on economic growth, and capital expenditure has a positive and significant effect on economic growth. However, the Sobel test shows that capital expenditure does not significantly mediate the relationship between regional financial capacity and economic growth. Conclusions: The effect of regional financial capacity on economic growth in Biak Numfor Regency occurs predominantly through a direct channel rather than through capital expenditure. Limitations: The single-region time series design over a ten-year period limits generalizability, and capital expenditure is measured in aggregate rather than disaggregated by sector. Contributions: The study offers empirical evidence on the limits of capital expenditure as a transmission channel from local fiscal capacity to economic growth in a small, resource-dependent island regency, informing more targeted regional budget allocation policy.